Intrapreneurship with Nishant Raj (Assemble You, 2023)
In this episode of the Power Skills Project, Adam interviews Nishant Raj about his journey as an intrapreneur. Nishant is an agile practitioner focused on data-driven innovation in manufacturing. His passion is around bridging the adoption of Web 3.0 to solve relevant manufacturing and supply chain problems. Nishant has been practising intrapreneurship in his previous roles before very recently taking the plunge and striking out on his own. In this episode he walks us through why intrapreneurship is so important and how to innovate, test and grow within a larger company structure. This episode is full of tips for budding intrapreneurs and business leaders who want to nurture and encourage innovation. Enjoy!